Increased production of Interleukin 1 by peripheral monocytes activated with biliary antigen immune complex in primary biliary cirrhosis - MAEDA, Takashi; ITO, Kenichi; MIYAZAKI, Masako; SAIBARA, Toshiji; ONISHI, Saburo; YAMAMOTO, Yasuro (Kanzo, 1985)
This study was to define the immunological role of increased circulating immune complex in primary biliary cirrhosis (PBC). We studied the production of Interleukin 1 (IL-1) by peripheral blood monocytes from 6 primary biliary cirrhosis patients. Results were compared with those obtained from 10 healthy volunteers. Monocytes from PBC patients, activated with human IgG immune complex, were found to yield increased amount of IL-1. And monocytes from PBC patients, activated with biliary antigen immune complex, were found to yield significantly increased amount of IL-1. As macrophages around the destructed bile ducts may be stimulated with biliary antigen immune complex in vivo, our findings of increased production of IL-1 with the stimulation of immune complex may contribute to the understanding of the pathogenesis of chronic nonsuppurative destructive cholangitis.